Developing Metacognitive Writing Strategy to Enhance Writing Skills Viewed from Prospective Teachers' Critical Thinking Skills - Mohammad Kazemian; Lalu Ari Irawan; Haerazi Haerazi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The metacognitive awareness and critical thinking skills were essential to be subjected to the prospective teachers to regulate their learning and train how to practice writing effectively. This study was aimed at developing the model of the metacognitive writing strategy to improve prospective teachers' writing skills viewed from critical thinking skills in Indonesian higher education. To attain the research aim, the research and development (R&D) study was employed. The stages of R&D design included defining, designing, developing, and disseminating. To attest to the effectiveness of the metacognitive writing strategy, the researcher used a quasi-experimental design in the form of pre-test and post-test control group design. The prospective teachers were divided into two groups, the experimental and control group. The experimental group was treated using the metacognitive writing strategy, while the control group was taught using the conventional strategy. The instruments of collecting data used the metacognitive writing test and critical thinking test. Then, the data were analysed using descriptive and inferential statistical devices. The results of the study showed that the metacognitive writing strategy can help prospective teachers to regulate their learning activities in terms of what and how to write in the class. At the top of that, they are able to compose good exposition texts. It was proven that the average score of learners in the experimental class was higher than those on the control class. The research findings were elaborated in the research discussion.